Вплив приелектродного імпедансу ємнісного сенсора на результат вимірювання складових імітансу - Походило, Є. В.; Герасим, М. Р.; Піцюра, В. І. (Видавництво Львівської політехніки, 2018)
Проаналізовано вплив приелектродного імпедансу ємнісного сенсора, утвореного ємністю подвійного шару та імпедансом Варбурга, на результат вимірювання активної та реактивної складових імітансу (імпедансу та адмітансу) електролітичних об’єктів у частотному діапазоні тестового сигналу. Показано, що реактивна складова приелектродного імпедансу на низьких частотах залежить лише від ємності подвійного шару. Активна складова приелектродного імпедансу на низьких частотах визначається опором, утвореним ємністю подвійного шару та відношенням до неї поляризаційної ємності, завдяки чому вплив приелектродної ємності на активну складову приелектродного імпедансу послаблюється. На вищих частотах активна складова залежить від аналогічного опору, а також від тангенса кута паралельного з’єднання ємності подвійного шару та поляризаційного опору. Відповідно до цього приелектродний імпеданс можна подати спрощеною схемою заміщення відповідно до режиму вимірювання. Наведено відповідні спрощені схеми заміщення контактного ємнісного сенсора з об’єктом контролю, поданим двоелементною паралельною схемою заміщення.

Influence of near-electrode impedance of capacitive sensor on result of measuring the active and reactive components of the admittance of electrolytic objects is considered. Near-electrode impedance is formed by capacity of the double layer and the Warburg impedance (polarization capacitance and resistance). Reactive and active components of admittance are the informative parameters of object’s electro physical parameters, in particular dielectric permittivity and specific conductivity. Product quality is assessed by comparing the reactive and active object components of the impedance or admittance with the corresponding parameters of the standard samples. Significant influence on the result of measuring immittance components of such objects is fixed at low frequencies. However, we need to measure the electro physical quantities at the mentioned frequencies. So we develop the mathematical models of reactive and active components at different frequencies and analyse the obtained results for evaluating the effect of near-electrode impedance. Different impact of the near-electrode impedance parameters on its active and reactive components is revealed. It is shown that at low frequencies the reactive component of the near-electrode impedance depends on the double layer capacity and does not depend on the parameters of the Warburg impedance. However, the active component of the near-electrode impedance at low frequencies is determined by the resistance formed by the capacity of the double layer and the ratio to it of the polarization capacitance. Due to this the impact of the electrode capacitance on the active component of the electrode impedance is weakened. At higher frequencies, the active component depends on similar resistance as well as on the tangent of the parallel connection angle of the double-layer capacity and polarization resistance. Corresponding equivalent circuits of the contact capacitive sensor with the measured object are given. The last one taking into account with the near-electrode impedance effect and is considered by the two-element substitution scheme. The obtained mathematical models for the reactive impedance and admittance components of measured object in a wide frequency range for such schemes are analysed. It is shown that at low frequencies the reactive component of both impedance and admittance is determined predominantly by the double layer capacity. At higher frequencies prevails the capacity of the measured object. Such a transition from low frequencies to higher is accompanied with the fact that reactive component acquires extreme values in the frequency range. This may be an identification feature of the objects non-electric nature of different origins. Replacement schemes of the contact capacitance sensor with the measured object for the mode of measuring the active component at low and high frequencies are given. Corresponding mathematical models of active components of such schemes in the frequency range are obtained and analysed. Regarding the research of mathematical models of active and reactive components of immittance control objects of nonelectric nature, in particular electrolytic substances the conclusions are fulfilled. In order to reduce the methodological error it is not recommended to apply the substitution scheme of the contact capacitance sensor, since the impact of the parameters of electrode impedance differs for inadequate measuring modes. Therefore, for theoretical analysis of mathematical models of immittance active and reactive components of measuring object is recommended the appropriate substitution scheme. Similarly, it is possible to develop the similar schemes of a contact sensor with objects provided by multi-element bipolars. Taking into account the above mentioned, it can be obtained the adequate results of the measuring and simulating studies.
Influence of near-electrode impedance of capacitive sensor on result of measuring active and reactive components of immitance
Keywords: ємнісний сенсор; приелектродний імпеданс; ємність подвійного шару; об’єкт кваліметрії; комплексна похибка; імпеданс; адмітанс; імпеданс Варбурга; capacitive sensor; near-electrode impedance; double layer capacity; qualimetry object; complex error; impedance; admittance; Warburg impedance